Competência social e arteterapia em um programa de intervenção na escola - Norgren, Maria de Betânia Paes (2009)
The world has changed, the interpersonal relations has been modified, so have the hearing practices, the values and the reality representations. It is necessary to develop interventions that help people to deal with the modern life complexity, challenges, crises and transitions. This study had the motive to develop and evaluate a social emotional competence program done with purpose to facilitate in short term the transition from 4th to 5th grade in a public school. The method used was the intervention-research, in a social clinic context. In spite of, not leading to any assurance, insist on a personal comprehension of the world, of himself and as change agent; emphasizes subject singularity and implies the researcher in the quest of structure, meaning and intervention. (Lévy, 2001; Sèvigny, 2001). Art therapy knowledge, creativity health promotion and social emotional learning, on a contextualized perspective were used to elaborate the program. The program begun with demand construction and students, parents and teachers were interviewed. The intervention lasted eighteen meetings and dealt with the following themes: change and growing as human development stages; self knowledgement; interpersonal relations; problem and conflict resolution techniques and creativity. At the first phase, on 2007, 75 students on the 4th grade participated. On the next year, four months after the school change, 68 students were evaluated: at those, 41 had participated on the intervention and 27 came from other schools and becoming control group. They were evaluated on the following aspects: scholar performance, absence rate, sociometric evaluation, network chart (Sluski, 1997), school description, drawings, teacher s perception and evaluation, parent s interview. Most of the students that participated at the program have showed better than or at least as expected performance, confirming that the intervention contributed to student s adaption on a short term, being effective on developing social emotional abilities